IMPLEMENTASI KEGIATAN FUN LEARNING DALAM COOKING CLASS KURIKULUM MERDEKA DI POCENTER - Madina, Bidarianti M; Kristiana, Dian (INDOPEDIA (Jurnal Inovasi Pembelajaran dan Pendidikan), 2025)
Early childhood education (PAUD) is very important in laying the foundation for children's growth and development in this era of globalization and technological progress. The "fun learning" method or also called enjoyable learning is one strategy that can be used to foster a more positive interest in learning among children. This research aims to describe the implementation of fun learning in the Merdeka Curriculum cooking class activities at Pocenter. By using descriptive techniques, researchers can describe or explain events based on field facts. This is related to the problem studied, namely the use of fun learning in the independent curriculum cooking class activities at Pocenter. The research subjects were teachers and children who took part in fun learning activities in the Pocenter culinary class. Researchers in this study used a direct observation strategy as an instrument and data collection method, namely seeing subjects in their natural state. The research results show that cooking classes can develop fine motor skills through cutting, squeezing, forming and molding movements. Young people can gain skills in creativity, safety and hygiene. Be able to explain the various types of vegetables and the importance of consuming them every day.